If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 + 3x = 9 Reorder the terms: -5 + 4x + 3x = 9 Combine like terms: 4x + 3x = 7x -5 + 7x = 9 Solving -5 + 7x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 7x = 9 + 5 Combine like terms: -5 + 5 = 0 0 + 7x = 9 + 5 7x = 9 + 5 Combine like terms: 9 + 5 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| 4q=7q+37 | | 1.5-0.25(a+4)=3+(.05-0.5a) | | 4t^2+18t-400=0 | | -20=-7x+1 | | 5(-4x-3)=13x+9 | | -50-7x=-3x+62 | | 312x+51=33 | | 4c-7=3c | | 9x+10y=-16 | | 9y-15=-2(y-6) | | 34+5n=9 | | 20-2n=80 | | 3d-4(5d-8)=-12-6d | | 2x+(2x-1)=31 | | 5x+7+3x=-1 | | 8(x+2)=-6(x+5) | | (2x+9)(4x+2)= | | 15m+3m=-18 | | 12y=3(4y-7) | | 10b-9b=2 | | 4-2(3X-2)=2(X-3) | | 8v+12=4(2v+3) | | 2+x*3+2x=21 | | 8x^2+-14x+3=0 | | 1.3p+1=1.6 | | 3x-2x+1=5 | | 62=x-6x+2 | | 7=1x(3+2x) | | -8+4x+4x=-88 | | 2(4x-3)-7(x+1)= | | 10+12x=3(5+3x)-3 | | 175=175-2.75n |